Exploring the Influence of Social Support and Personality on Employee Well-being: The Mediating Role of Transformational Leadership at PT. Cakrawala Dinamika Utama - Marta Nurtemani Zega; Emi Wakhyuni doping; Wilchan Robain (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to analyze the influence of social support and personality on the implementation of employee well-being, with transformational leadership style as an intervening variable, at PT. Cakrawala Dinamika Utama. We use a quantitative approach, utilizing survey techniques and structural equation modeling (SEM) analysis to test the relationship between variables. The study population includes all permanent employees of PT. Cakrawala Dinamika Utama Medan at the Soho Bar and Resto unit, totaling 105 people. We used the census sampling method to sample the entire population. Thus, the sample in this study was 105 respondents. The results of the study are expected to provide strategic insights for companies in designing policies that support employee well-being by considering aspects of social support, personality, and adaptive leadership style. These findings are also expected to be able to increase the effectiveness of employee well-being programs at PT. Cakrawala Dinamika Utama, as well as contribute to improving employee performance and job satisfaction in a sustainable manner.